228k views
1 vote
-3(x-14)+9x=6x+42
what does that equal​

User Memento
by
5.0k points

2 Answers

4 votes
answer: 0=0 it’s an identity
User Yandry
by
5.7k points
4 votes

-3(x-14) + 9x = 6x + 42

Subtract 6x to the other side of the equation, along with subtracting 42

-3(x - 14) + 9x - 6x - 42

Deal with the -3(x-14)

-3x + 42 + 9x - 6x - 42

Combine like terms

-3x + 9x - 6x = 0

42 - 42 = 0

0 = 0

Your answer is Infinitely Many Solutions

User Drysdam
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.